A Critical Estimate of Khuswant Singh’s Fiction: An Assessment of Khuswant Singh's Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Khuswant Singh is one of the finest historian and novelists, a forthright political commentator, and an outstanding observe and social critic. His reputation as a writer of Indo English fiction rests upon his novels like “train to Pakistan, I shall not Hear the Nightingale, Delhi, The company of women and burial at sea.” He has written short stories as “The voice of God.” A Bride for the sahib” and Blank Jasmine.” No doubt, Khuswant Singh is a convenient write in the sense that he does not compel a wider reading.